Buprenorphine Patch as a Bridge to Sublingual Treatment of Opioid Use Disorder in Pregnancy. Issue 4 (April 2021) - Galati, Bridget M.; Carter, Ebony B.; Perez, Marta; Russell, Sharman; Nazeer, Sarah; Raghuraman, Nandini; Kelly, Jeannie C.
Abstract : Pregnant patients with opioid use disorder completed buprenorphine induction with a transdermal patch bridge to sublingual dosing and reported experiencing no or mild withdrawal symptoms.